A thermosiphon photobioreactor for photofermentative hydrogen production by Rhodopseudomonas palustris. - Bosman, Catharine Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.